Magnetic Field Gradient Across the Flank Magnetopause - Němeček, Zdeněk; Grygorov, Kostiantyn; Šafránková, Jana; Šimůnek, Jiří; Pi, Gilbert (Frontiers in Astronomy and Space Sciences, 2021)
Magnetic pressure inside the magnetopause is usually balanced with a sum of thermal plasma and magnetic pressures on the magnetosheath side. However, observations reveal that the magnetosheath magnetic field can be frequently larger than that in the magnetosphere (inverse magnetic field gradient across the magnetopause) and thus the enhanced pressure from the magnetosheath side seems to be uncompensated. Such events are rare in the subsolar region but their occurrence rate increases toward flanks. The analysis based on statistical processing of about 35,000 THEMIS magnetopause crossings collected in course of the 2007-2017 years shows that these events are more frequently observed under enhanced geomagnetic activity that are connected with a strong southward IMF. Case studies reveal that such state of the magnetopause boundary layers can persist for several hours. The paper discusses conditions and mechanisms keeping the pressure balance across the magnetopause under these conditions.